The Accountability of the National Land Agency (BPN) in Land Ownership Disputes Due to Overlapping Rights - Zhulfani Junnaika Wibowo; Sunny Ummul Firdaus; Noor Saptanti (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This legal research aims to determine the responsibility of the National Land Agency for disputes over overlapping ownership of land rights. This research uses normative research by analyzing the form of responsibility of the National Land Agency for the issuance of multiple certificates that cause disputes in the community. This research uses primary legal materials obtained from legislation, official records and judges' decisions and secondary legal materials obtained from dictionaries, books and journals. The results of this study show that the form of responsibility of the National Land Agency (BPN) is divided into several forms, namely civil responsibility, criminal responsibility, and administrative responsibility. Overlapping certificates must be canceled based on a court decision that has permanent legal force.